A percolation-based micromechanical model for elastic stiffness and conductivity of foam concrete - Wang, Fengjuan; Xin, Zhongyi; Jiang, Jinyang; Sui, Shiyu (Frontiers in Physics, 2023)
Understanding the effects of void morphology and percolation on the physico-mechanical properties of foam concrete is of great interest in the evaluation of service-life of civil and hydraulic infrastructures. It has been a key but unresolved issue how to accurately probe the percolation threshold of complex void network, and the dependence of elastic modulus and conductivity of foam concrete on void configurations. In this work, we focus on the prolate spheroidal void morphologies with the aspect ratios of 2.5 and 2, following the microscopic measurements reported in the literature. We present a Monte Carlo finite-size scaling analysis to capture the percolation thresholds of voids with both morphological types, and of spherical voids as a benchmark to test the accuracy and reliability of the proposed numerical strategy by comparing against the existing numerical results in literature. Furthermore, this work proposes a simple and powerful percolation-based micromechanical model for precisely predicting the elastic modulus and thermal conductivity of foam concrete in the whole range of porosities, including near the percolation threshold. It can be convinced of a general micromechanical framework to elucidate the intrinsic relationship of void morphology and percolation to the physico-mechanical properties of concrete, which is readily applicable to other percolating networks composed of inter-penetrable inhomogeneities like cracks, pores, interfaces, capsules and tunneling networks.